Narrative, Philosophy and Life - Speight, Allen (Springer, 2015)
​This notable collection provides an interdisciplinary platform for prominent thinkers who have all made significant recent contributions to exploring the nexus of philosophy and narrative. It includes the latest assessments of several key positions in the current philosophical debate. These perspectives underpin a range of thematic strands exploring the influence of narrative on notions of selfhood, identity, temporal experience, and the emotions, among others. Drawing from the humanities, literature, history and religious studies, as well as philosophy, the volume opens with papers on narrative intelligence and the relationship between narrative and agency. It features special sections of in-depth commentary on a range of topics. How, for example, do narrative and philosophical biography interact? Do celebrated biographical and autobiographical accounts of the lives of philosophers contribute to our understanding of their work? This new volume has a substantive remit that incorporates the intercultural religious view of philosophy’s links to narrative together with its many secular aspects. A valuable new resource for more advanced scholars in all its constituent disciplines, it represents a significant addition to the literature of this richly productive area of research.